BH3‐in‐groove dimerization initiates and helix 9 dimerization expands Bax pore assembly in membranes. (23rd December 2015) - Zhang, Zhi; Subramaniam, Sabareesh; Kale, Justin; Liao, Chenyi; Huang, Bo; Brahmbhatt, Hetal; Condon, Samson GF; Lapolla, Suzanne M; Hays, Franklin A; Ding, Jingzhen; He, Feng; Zhang, Xuejun C; et al.
Abstract: Pro‐apoptotic Bax induces mitochondrial outer membrane permeabilization (MOMP) by forming oligomers through a largely undefined process. Using site‐specific disulfide crosslinking, compartment‐specific chemical labeling, and mutational analysis, we found that activated integral membrane Bax proteins form a BH3‐in‐groove dimer interface on the MOM surface similar to that observed in crystals. However, after the α5 helix was released into the MOM, the remaining interface with α2, α3, and α4 helices was rearranged. Another dimer interface was formed inside the MOM by two intersected or parallel α9 helices. Combinations of these interfaces generated oligomers in the MOM. Oligomerization was initiated by BH3‐in‐groove dimerization, without which neither the other dimerizations nor MOMP occurred. In contrast, α9 dimerization occurred downstream and was required for release of large but not small proteins from mitochondria. Moreover, the release of large proteins was facilitated by α9 insertion into the MOM and localization to the pore rim. Therefore, the BH3‐in‐groove dimerization on the MOM nucleates the assembly of an oligomeric Bax pore that is enlarged by α9 dimerization at the rim. Synopsis: Apoptotic Bax oligomers permeabilize the mitochondrial outer membrane. Structural analyses and modeling of Bax interactions at mitochondria show that BH3‐in‐groove dimerization on membranes initiates the pore assembly, which is followed by helix 9 dimerization‐mediated expansion. Bax protein oligomerization initiates with helices α2‐α5 forming a BH3‐in‐groove dimer interface on the membrane surface. The BH3‐in‐groove dimer interface is rearranged after α5 insertion into the membrane. α9 helices from neighboring Bax molecules form another dimer interface inside the membrane linking the BH3‐in‐groove dimers to higher order oligomers. α9 insertion and dimerization facilitate pore enlargement required to release large mitochondrial intermembrane space proteins. Abstract : Apoptotic Bax oligomers permeabilize the mitochondrial outer membrane. Structural analyses and modeling of Bax interactions at mitochondria show that BH3‐in‐groove dimerization on membranes initiates the pore assembly, which is followed by helix 9 dimerization‐mediated expansion.